Knowledge of and concern about global biodiversity loss vs local biodiversity loss in the Maputaland-Pondoland-Albany Hotspot (MPA) - Toyisi, Zanele Jacqueline (Rhodes University, Faculty of Science, Department of Environmental Science)
Biodiversity forms the basis of the ecosystem services that society depends on. However, humanity has caused an increase in the extinction rates up to 100 times higher than that of evolutionary background levels. Recent studies found that biodiversity conservation becomes successful when it is grounded in local support. Support for conservation of biodiversity depends on peoples' knowledge of biodiversity, their attitudes and awareness of the number of species that are present and that are threatened with extinction. However, some studies have shown that the public has little knowledge about the concept of biodiversity and have poor biodiversity identification skills. There is growing concern that people know and are more concerned about global biodiversity loss than what is happening around them locally. The notion that people know and are more concerned about global biodiversity loss rather than local, has not been deeply studied. Most studies have been in developed countries, with limited studies in developing countries and countries that have high diversity such as South Africa. Having accurate knowledge about biodiversity and the environment is said to be the key predictor of intention to change behaviour in relation to biodiversity. Therefore, the purpose of this study was to understand the knowledge and concern (if any) people have of biodiversity at global and local scales. More so, it set out to determine how familiar people are with the term biodiversity, what they consider as forces leading to biodiversity decline, the level of concern that they have for biodiversity loss and if knowledge and concern is influenced by demographic profiles. To achieve this aim, a total of 220 random interviews were conducted in three towns within the Maputaland-Pondoland-Albany Hotspot in South Africa. The results show that respondents are familiar with the term biodiversity. There was a strong relationship between having heard of the term and the ability to define it with 55 % of the respondents aware of it and able to define it. Respondents had moderate knowledge general knowledge related to biodiversity. Gender, education and childhood background did play a role in the knowledge of biodiversity. Women had more knowledge about biodiversity than men, highly educated respondents knew more and the youth knew more than older respondents. The results of this study found that there were no respondents who could not name any local species from South Africa. However, things changed at global level with 32 % of the participants unable to name species at global level. Endangered species are still relatively unknown, as the majority of respondents could not name any at district (84 %) or at global level (61 %). Charismatic species were known the most by respondents as 52 % mentioned them at national level and 59 % at global level. This study also assessed if there is concern for biodiversity loss. The results showed that there is concern for biodiversity with 71 % of the respondents in support for conservation and 60 % of the respondents willing to donate towards conservation. This study found that reasons for conservation related to the level of products consumed directly from the environment. Those that supported conservation for use values consumed more products from the environment than those who were in support for non-use values. Furtherly, this study found that women were more concerned about biodiversity loss than men. Highly educated respondents were more concerned and the youth was not. Furtherly, this study found that knowledge about biodiversity loss corelated with concern. For example, women had more knowledge and were more concerned about biodiversity loss. Overall, this study has shown that there is some knowledge and concern that people have about biodiversity and its loss. This can assist the relevant policy makers and researchers to know where intervention is needed to increase the knowledge that people have of biodiversity loss and which aspects of biodiversity people are most concerned about. This is so that new policies and conservation measures can include what is appealing to the local people so that support for conservation can be built and accepted by local people.
Keywords: Biodiversity Public opinion; Biodiversity conservation -- South Africa; Maputaland-Pondoland-Albany Hotspot; Biodiversity loss; Local knowledge